Rectal ultrasound with fine needle aspiration: an underutilized modality for delineating and diagnosing perirectal, presacral, and pelvic lesions - Brown, Landon K.; Clark, Norman R.; Conway, Jason; Mishra, Girish (Endoscopy International Open, 2019)
Background and study aims The merits of rectal ultrasound for rectal cancer staging are well documented. Conventional approaches to accessing perirectal and presacral lesions entail computed tomography guidance via a transgluteal approach or frank surgical exploration. We report on the safety and efficacy of performing rectal ultrasound with fine-needle aspiration (RUS-FNA) for evaluating perirectal, presacral, and pelvic abnormalities. Patients and methods Patients who underwent RUS-FNA of perirectal, presacral, or pelvic lesions between August 2005 and September 2016 were identified using an institutional database. Subjects were all individuals treated at Wake Forest Baptist Medical Center in Winston-Salem, North Carolina, United States. Patient demographics and imaging characteristics were noted. Procedural details included lesion size, location, echo appearance, and technical information. Patients were given antibiotics prior to FNA attempt and for 3 days after. Diagnostic yield, clinical utility, and complications were noted. Results Twenty-seven patients met criteria during the specified study time period. The cohort consisted of 12 males (44.4 %) and 15 females (55.5 %). RUS-FNA was diagnostic in 24 patients (88.8 %) and obviated the need for surgery in 14 patients (51.9 %). There were four complications (14.8 %): two perirectal and two presacral abscesses. Conclusion While the diagnostic yield of RUS-FNA is high and the potential to affect clinical decision-making is substantial, risk of complication is not negligible. RUS-FNA should only be performed if the result will substantially alter clinical management, and the decision to perform RUS-FNA should be made with close consultation between the endosonographer, surgeon, and/or medical or radiation oncologist.